Occurrence and characteristics of extended-spectrum-β-lactamase- and pAmpC-producing Klebsiella pneumoniae isolated from companion animals with urinary tract infections. - Megan Min Yi Lee; Nan-Ling Kuan; Zhi-Yi Li; Kuang-Sheng Yeh (PLoS ONE, 2024)
This study examined 70 Klebsiella pneumoniae isolates derived from companion animals with urinary tract infections in Taiwan. Overall, 81% (57/70) of the isolates carried extended-spectrum β-lactamase (ESBL) and/or plasmid-encoded AmpC (pAmpC) genes. ESBL genes were detected in 19 samples, with blaCTX-M-1, blaCTX-M-9, and blaSHV being the predominant groups. pAmpC genes were detected in 56 isolates, with blaCIT and blaDHA being the predominant groups. Multilocus sequence typing revealed that sequence types (ST)11, ST15, and ST655 were prevalent. wabG, uge, entB, mrkD, and fimH were identified as primary virulence genes. Two isolates demonstrated a hypermucoviscosity phenotype in the string test. Antimicrobial susceptibility testing exhibited high resistance to β-lactams and fluoroquinolones in ESBL-positive isolates but low resistance to aminoglycosides, sulfonamides, and carbapenems. Isolates carrying pAmpC genes exhibited resistance to penicillin-class β-lactams. These findings provide valuable insights into the role of K. pneumoniae in the context of the concept of One Health.